The Role of the CXCL12/CXCR4/ACKR3 Axis in Autoimmune Diseases - García-Cuesta, Eva M.; Santiago, César A.; Vallejo-Díaz, Jesús; Juarranz, Yasmina; Rodríguez-Frade, José Miguel; Mellado, Mario (Frontiers in Endocrinology, 2019)
Chemokine receptors are members of the G protein-coupled receptor superfamily. These receptors are intimately involved in cell movement, and thus play a critical role in several physiological and pathological situations that require the precise regulation of cell positioning. CXCR4 is one of the most studied chemokine receptors and is involved in many functions beyond leukocyte recruitment. During embryogenesis, it plays essential roles in vascular development, hematopoiesis, cardiogenesis and nervous system organization. It has been also implicated in tumor progression and autoimmune diseases and, together with CD4, is one of the co-receptors used by the HIV-1 virus to infect immune cells. In contrast to other chemokine receptors that are characterized by ligand promiscuity, CXCR4 has a unique ligand – stromal cell-derived factor-1 (SDF1, CXCL12). However, this ligand also binds ACKR3, an atypical chemokine receptor that modulates CXCR4 functions and is overexpressed in multiple cancer types. The CXCL12/CXCR4/ACKR3 axis constitutes a potential therapeutic target for a wide variety of inflammatory diseases, not only by interfering with cell migration but also by modulating immune responses. Thus far, only one antagonist directed against the ligand-binding site of CXCR4, AMD3100, has demonstrated clinical relevance. Here, we review the role of this ligand and its receptors in different autoimmune diseases.